Preparation and Characterization of Cellulose Film from Velvet Tamarind Rind (Dialium indum L.) for Food Packaging - Kacaribu, Andriy Anta; Rahmi; Julinawati; Fathana, Haya; Reza, Muhammad; Iqhramullah, Muhammad (Applied Science and Engineering Progress, 2025)
The environmental impact of plastic waste underscores the need for biodegradable films as sustainable alternatives. This study investigates velvet tamarind rind as a novel cellulose source, extracted through chemical and ultrasound treatments. The isolated cellulose exhibited good characteristics, with crystallinity indices of 66% and 85.4% for chemical and ultrasound treatments, respectively. Three types of cellulose films were prepared: Cell film (without ultrasound treatment), CellS film (with ultrasound treatment), and CellSP film (with ultrasound treatment and glycerol as a plasticizer). The CellS film exhibited a higher crystallinity index (85.4%) than the Cell and CellSP films (62.7% and 51.8% respectively). The addition of glycerol in the CellSP film resulted in the highest tensile strength of 17.2 MPa and a smoother surface compared to the other films. Notably, the organoleptic profile of grapes wrapped with the CellSP films showed comparable results to those grapes wrapped using polyvinyl chloride (PVC) wrap. These findings highlight the potential of velvet tamarind rind cellulose for eco-friendly food packaging, with properties that rival and, in some cases, surpass those of earlier studied wraps. Future work could explore scaling up production and enhancing performance through additional fillers or treatments.